Non-ionizing radiofrequency electromagnetic waves traversing the head can be used to detect cerebrovascular autoregulation responses - Oziel, M.; Hjouj, M.; Gonzalez, C. A.; Lavee, J.; Rubinsky, B. (Scientific reports, 2016)
Monitoring changes in non-ionizing radiofrequency electromagnetic waves as they traverse the brain can detect the effects of stimuli employed in cerebrovascular autoregulation (CVA) tests on the brain, without contact and in real time. CVA is a physiological phenomenon of importance to health, used for diagnosis of a number of diseases of the brain with a vascular component. The technology described here is being developed for use in diagnosis of injuries and diseases of the brain in rural and economically underdeveloped parts of the world. A group of nine subjects participated in this pilot clinical evaluation of the technology. Substantial research remains to be done on correlating the measurements with physiology and anatomy.